Russia's Innovation Reform - The Current State of the Special Economic Zones - - Kari Liuhto (Revista de Management Comparat International, 2009)
Approximately 20 special economic zones (SEZs) have been founded in Russia. Four of them are innovation zones, two manufacturing zones, seven tourism zones, three port zones and two old zones of the 1990's, namely the Kaliningrad SEZ and the Magadan SEZ. Additionally, four gambling zones are to be opened by July 2009. The Russian SEZs currently produce more plans than results i.e. unrealistic plans characterise the contemporary Russian SEZs. Only the Kaliningrad SEZ and the Magadan SEZ can be classified as fully operational, and therefore, it is far too early to make any firm conclusion on the economic impact of these zones on the Russian economy. On the other hand, it is highly recommendable that a follow-up of the Russian SEZs will be carried out in 3-5 years from now, since the results of today do not necessarily describe the potential of tomorrow.